Sustainability reporting through environmental, social, and governance: a bibliometric review - Mathew Kevin Bosi; Nelson Lajuni; Avnner Chardles Wellfren; Thien, Sang Lim (MDPI, 2022)
Research on sustainability reporting is becoming increasingly important. Despite the growing body of literature on sustainability reporting, little is known about its past trends and how research areas might evolve in the future. Recognizing and understanding the research trend related to sustainability reporting will enable future researchers to plan and conduct research that is of high interest and impact in terms of both readership and citations. This study examines a large body of literature on environmental, social, and governance (ESG) and sustainability reporting over the last 24 years (1998–2022). The study used bibliometric analysis using VOSviewer software to perform publication trends, citation analysis, and keyword mapping analysis. Data for the analysis was extracted from the online database Scopus on 24 April 2022. Uniquely, the study also employed the Gephi technique, version 0.9.5 of bibliometric analysis, to uncover past ESG research trends and sustainability reports and predict how the content of these study areas will evolve in the future. Based on a sample size of 358 articles, most publications were published in English and in open-access journals. The resultant outcomes of the Gephi technique show that the ESG and sustainability reports can be merged into four clusters. The first cluster points out that corporate social responsibility (CSR) and sustainability reporting now have a stronger social focus as they focus on benefits and environmental impacts. The second cluster focuses on benefits and corporate social responsibility rewards. The third cluster emphasizes the cost of equity and ESG disclosure. Finally, the fourth cluster emphasizes the cost of capital and governance in CSR. The research cluster’s discovery sheds light for future researchers in planning and designing future research focuses.